2009
DOI: 10.1002/cncr.24041
|View full text |Cite
|
Sign up to set email alerts
|

Leptomeningeal carcinomatosis

Abstract: BACKGROUND:Leptomeningeal carcinomatosis (LC) represents a devastating complication of systemic cancer, and patients with LC have a dismal prognosis and increased mortality. The few studies that have focused on the evaluation of prognostic factors in patients with LC have resulted in contradictory results. Thus, the treatment of LC remains controversial, and no straightforward guidelines exist in the literature. The objective of the current study was to identify prognostic markers related to LC survival to bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 33 publications
(49 reference statements)
3
20
0
1
Order By: Relevance
“…According to manifesting symptoms, Boogerd et al (15) and Balm et al (18) demonstrated that patients with symptoms related to cranial nerve or cerebral involvement had worse prognosis, respectively. However the relationship between symptoms and outcomes was conflicted with each other studies (15, 16, 19). Although the neuraxis imaging study is one of most important diagnostic tools for LM, it is unclear whether extent of CNS infiltration on imaging study affects the survival.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…According to manifesting symptoms, Boogerd et al (15) and Balm et al (18) demonstrated that patients with symptoms related to cranial nerve or cerebral involvement had worse prognosis, respectively. However the relationship between symptoms and outcomes was conflicted with each other studies (15, 16, 19). Although the neuraxis imaging study is one of most important diagnostic tools for LM, it is unclear whether extent of CNS infiltration on imaging study affects the survival.…”
Section: Discussionmentioning
confidence: 93%
“…In the past, IT-CTx was considered as the main treatment modality in LM, whereas the role of Sys-Tx was questioned due to belief that intravenously injected chemotherapeutic agents was unavailing because of BBB (13). Thus, older studies mainly focused on validating the role of IT-CTx (18, 19, 20, 22, 23). Recently, however, the role of IT-CTx has been questioned.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore remarkable that little consensus exists amongst different laboratories about the reference ranges for CSF glucose and lactate [1]. CSF glucose is decreased in, amongst others, patients with bacterial meningitis and leptomeningeal carcinomatosis, usually in combination with other abnormal CSF parameters, such as an elevated leucocyte count, total protein or lactate concentration [2][4]. Low CSF glucose, often in combination with low CSF lactate, can also be found in patients with GLUT1 deficiency syndrome, a treatable genetic metabolic disorder that is caused by impaired glucose transport into brain [5].…”
Section: Introductionmentioning
confidence: 99%
“…proper treatment can prevent the deterioration of neurologic symptoms that impair the patient's quality of life. 1,6 Therefore, early diagnosis and proper treatment of LC are the most important strategies to improve the overall survival and quality of life of patients with LC.…”
mentioning
confidence: 99%